Resemiotization: tracing the movement of resources in landscape architectural design trajectories. (February 2023) - Price, Christine; Archer, Arlene
University students in landscape architecture need to mobilize a range of resources in their design trajectories in order to resolve their designs. Often design education settings are influenced by design traditions of the global north, and thus may favour particular ways of knowing. This article aims to contribute to a multimodal pedagogy for diversity exploring the ways in which diverse students mobilize resources to move between spatial, verbal and visual modes in a landscape architectural design trajectory. It specifically traces the resources that one student brings to her learning environment in a university in South Africa, and identifies the experiential, social, semiotic, interactive and pedagogical resources she deploys. The authors demonstrate how these resources shape and prompt the student's meaning-making processes, and how she mobilizes these resources to move her design trajectory forward. They do this by building on Kress and Van Leeuwen's Reading Images (2006) model of visual grammar, adapted for three-dimensional space, and Kress's notions of design in Multimodality (2010). The concept of resemiotization is key here to recognizing and understanding the meaning-making potential of modes. The authors argue that the affordances of different modes prompt resemiotization of resources at different times in the design trajectory, moving between material expression and nonmaterial (re)conceptualization. The processes of resemiotization can thus generate emergent meanings and transform them within the student's landscape design trajectories. This approach to pedagogy can valorize the agency, identity, ways of knowing and resourcefulness of diverse meaning-makers.